Aromatherapy for the prevention of postoperative nausea and vomiting: A systematic review and meta-analysis - Jian-Ying Wang; Hsueh-Yang Huang; Wan-O Chu; Tzu-Rong Peng; Ming-Chia Lee; Shih-Ming Chen; Jen-Ai Lee (Tzu Chi Medical Journal)
Objectives: Postoperative nausea and vomiting (PONV) are common complications following surgical procedures. While drug-based treatments are standard, there is increasing interest in nonpharmacological alternatives, such as aromatherapy, due to potential benefits and minimal side effects. This study aimed to assess the effectiveness of aromatherapy in preventing PONV. Materials and Methods: A comprehensive systematic review and meta-analysis were conducted using PubMed, Cochrane Library, EMBASE, and CINAHL databases for studies published up to May 2023. The included studies were randomized controlled trials (RCTs) and nonrandomized studies of interventions that examined the impact of aromatherapy on PONV. The risk of bias was assessed, and the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) approach was employed to evaluate the certainty of the evidence. Results: Eleven studies were selected for review, with eight RCTs included in the meta-analysis. Aromatherapy effectively reduced postoperative nausea severity (standardized mean difference [SMD]: −0.93, 95% confidence interval [CI]: −1.64 to −0.22; P = 0.010), but the reduction in vomiting episodes was not statistically significant (SMD: −0.81, 95% CI: −1.98-0.37; P = 0.180). Subgroup analysis indicated that ginger essence, lavender, and peppermint oils were particularly effective in managing postoperative nausea. However, due to significant statistical heterogeneity and potential biases in the studies, the results should be interpreted with caution. The certainty of the evidence, as evaluated by the GRADE approach, was low. Conclusion: Preliminary evidence supports the potential benefit of aromatherapy in reducing the severity of postoperative nausea. However, given the low certainty of current evidence, more rigorous and standardized research is needed. The safety, affordability, and potential benefits to patient comfort make aromatherapy a promising area for further research in postoperative care.